2019
DOI: 10.2478/fhort-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in peas (Pisum sativum L.) from Turkey asssessed with molecular and morphological markers

Abstract: The aim of this study was to identify the molecular and morphological characteristics of Turkish pea accessions (Pisum sativum L.). The genetic diversity among 130 Turkish landraces and 2 commercial varieties in a total of 132 pea accessions was assessed with 14 simple sequence repeat (SSR) markers. Forty-eight (48) polymorphic alleles were identified using 14 SSR markers. The pairwise Dice coefficients of similarity between accessions ranged from 0.091 to 0.960. The polymorphism information content (PIC) valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
2
13
1
Order By: Relevance
“…Therefore, the results of the genetic distance have shown that there is a room for the genetic improvement of these pea genotypes and the information generated can be utilized to make broad crosses and release new varieties. These findings collaborated with the earlier findings of Yirga et al (2013), Gixhari et al (2014), Georgieva et al (2016), Arif et al (2018), Hanci (2019), , Mohamed et al (2019) and Yumkhaibam et al (2019).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, the results of the genetic distance have shown that there is a room for the genetic improvement of these pea genotypes and the information generated can be utilized to make broad crosses and release new varieties. These findings collaborated with the earlier findings of Yirga et al (2013), Gixhari et al (2014), Georgieva et al (2016), Arif et al (2018), Hanci (2019), , Mohamed et al (2019) and Yumkhaibam et al (2019).…”
Section: Discussionsupporting
confidence: 89%
“…Field experiment of the present investigation was conducted in the Vegetable Experimental Research farm and molecular analysis was carried out at Department of Genetics, Faculty of Agriculture, Assiut University, Assiut, Egypt, during two successive years (October, 2017and October, 2018/2019 to evaluate the performance of 15 pea (Pisum sativum L.) genotypes which namely; Balmoral (P1), Dwarf Gray Sugar (P2), Little Marvel (P3), Master B (P4), Jacuar (P5), Progress No.9 (P6), Entesar 1 (P7), Meteor (P8), Early Perfection (P9), Cash (P10), Digrass (P11), Lincoln (P12), Victory Freezer (P13), Alaska (P14) and Deltafon (P15).…”
Section: Methodsmentioning
confidence: 99%
“…The SNP markers from two sequencing platforms, however, enumerated the existing genetic diversity similarly. The SNP markers quantified the current genotypes with an intermediate level of genetic variation compared to the previous studies in pea ( Burstin et al, 2015 ; Rana et al, 2017 ; Hanci, 2019 ). However, the higher genetic diversity reported by the abovementioned authors included pea accessions encompassing wild genotypes, landraces, and old cultivars collected worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…DNA based molecular markers are mainly used in the evaluation of genetic diversity [19,20]. Many marker techniques were developed for molecular characterization of pea (Pisum sativum L.) cultivars and populations [19,21,22] but SSR markers have been often preferred due to their high, level of polymorphism and reliability for pea (Pisum sativum L.) genetic diversity researches [1,20,23,24,25,26,27,28,29,30,31]. As rst approach we carried out Population STRUCTURE Analysis based on Bayesian statistics and evaluated using the ad hoc procedure [11] and [12] methods with admixture model.…”
Section: Resultsmentioning
confidence: 99%